Is stopping secondary prophylaxis safe in HIV‐positive talaromycosis patients? Experience from Myanmar. Issue 10 (1st August 2020) - Tun, N; Mclean, A; Deed, X; Hlaing, M; Aung, Y; Wilkins, E; Ashley, E; Smithuis, F
Abstract : Objectives: The aim of the study was to determine whether it is safe to stop secondary prophylaxis in patients with talaromycosis after immune reconstitution with a sustained increase in CD4 count to ≥ 100 cells/µL after antiretroviral therapy (ART). Methods: A retrospective cohort analysis was performed in HIV‐infected patients treated for talaromycosis between June 2009 and June 2017 in Medical Action Myanmar (MAM) clinics. Results: Among a cohort of 5466 HIV‐infected patients, 41 patients were diagnosed with and treated for clinical talaromycosis. All the patients were on ART and had a CD4 count < 100 cells/µL. Of these 41 patients, 24 patients (71%) were skin smear positive for talaromycosis, while results were negative in 17 patients. Median CD4 count and haemoglobin concentration were 24 cells/µL and 7.7 g/dL, respectively. Seventy‐three per cent (30) were male. Among the 41 patients, 11 (27%) died and six (15%) were transferred to other centres. Twenty‐four patients (58% of the total diagnosed) stopped itraconazole secondary prophylaxis after starting active ART with CD4 counts > 100 cells/µL for at least 1 year. Throughout the duration of follow‐up post itraconazole cessation, the observed incidence of relapse was zero with a total follow‐up of 93.8 person‐years (95% confidence interval 0–4 per 100 person‐years). The median (25th, 75th percentile) duration of follow‐up post‐prophylaxis discontinuation was 2.8 (2.1, 6.3) years. Conclusions: Secondary prophylaxis can be safely stopped in patients with talaromycosis after immune reconstitution with a sustained increase in CD4 count to ≥ 100 cells/µL after highly active antiretroviral therapy.